Biology and conservation of freshwater bivalves: past, present and future perspectives - Lopes-Lima, Manuel (2015)
Freshwater bivalves have been highly threatened by human activities, and recently their global decline has been causing conservational and social concern. In this paper, we review the most important research events in freshwater bivalve biology calling attention to the main scientific achievements. A great bias exists in the research effort, with much more information available for bivalve species belonging to the Unionida in comparison to other groups. The same is true for the origin of these studies, since the publishing pattern does not always correspond to the hotspots of biodiversity but is concentrated in the northern hemisphere mainly in North America, Europe and Russia, with regions such as Africa and Southeast Asia being quite understudied. We also summarize information about past, present and future perspectives concerning the most important research topics that include taxonomy, systematics, anatomy, physiology, ecology and conservation of freshwater bivalves. Finally, we introduce the articles published in this Hydrobiologia special issue related with the International Meeting on Biology and Conservation of Freshwater Bivalves held in 2012 in Bragança, Portugal.